Introduction: The Journal of Transport and Land Use enters year nine - David M Levinson (Journal of Transport and Land Use)
With this issue, the Journal of Transport and Land Use enters its ninth volume (and many articles from volume 10 can be found online under Forthcoming). Since our last update (Levinson 2013), JTLU has continued to grow and expand. Many of the articles in the issues in this and next volume were selected from papers presented at the 2014 World Symposium on Transport Land Use Research in Delft. We look forward to many more years of continued research and publication in this field.